E. Globulus Vessel and Fibre Chemical Analysis - Vaz, Álvaro; Coelho, João; Costa, Vera; Marques, Ana; Maloney, Thaddeus; Josphat, Phiri; Pinto, Paula; Oliveira, Ricardo; Simões, Rogério; Sousa, António (KnE Materials Science, 2022)
Hardwood species have a complex cellular structure consisting of fibres, vessel elements and parenchyma cells with different chemical compositions. However, the presence of vessels with significant dimensions in their structure is a recurrent problem in the operation of industrial UWF paper printing. Since the 1980s, vessel picking and ink refusal are problems that paper professionals have tried to solve, but solutions for these have not yet been fully found. If vessels are concentrated in a stream, they can be pre-treated (e.g., by mechanical refining) and reincorporated into the pulp. Other strategies aim at vessel enzymatic and/or chemical passivation and sheet surface chemical treatment, altering the vessel adhesion to the fibre network. This requires vessel concentration at laboratorial level for proper chemical studies, such as FE-SEM, μ-XPS, TOF-SIMS and μFTIR. The main objective of our experimental study was to examine bleached kraft pulp E. globulus vessel and fibre composition. For this we performed EDX and μ-FTIR analysis on both fibre and vessel elements, and obtained the carbohydrate composition, the total acids content, the hexenuronic acids content and the zeta potential. Keywords: E. globulus, vessel, EDX, μ-FTIR, sugar content, zeta potential